2011
DOI: 10.1021/es202211w
|View full text |Cite
|
Sign up to set email alerts
|

Unearthing Potentials for Decarbonizing the U.S. Aluminum Cycle

Abstract: Global aluminum demand is anticipated to triple by 2050, by which time global greenhouse gas (GHG) emissions are advised to be cut 50-85% to avoid catastrophic climate impacts. To explore mitigation strategies systematically, a dynamic material flow model was developed to simulate the stocks and flows of the U.S. aluminum cycle and analyze the corresponding GHG emissions. Theoretical and realistic reduction potentials were identified and quantified. The total GHG emissions for the U.S. aluminum cycle in 2006 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 22 publications
1
72
0
Order By: Relevance
“…Use: Aluminum is widely used in transportation, building, packaging, consumer durables, and many other sectors. Since most of the aluminum in final products has a long useful lifetime, aluminum accumulates in the technosphere and has the potential to become available as a future resource (Liu et al, 2011). It is estimated that three quarters of all the aluminum produced since the 1880s is still in productive use (Bertram et al, 2009a).…”
Section: Methodsmentioning
confidence: 99%
“…Use: Aluminum is widely used in transportation, building, packaging, consumer durables, and many other sectors. Since most of the aluminum in final products has a long useful lifetime, aluminum accumulates in the technosphere and has the potential to become available as a future resource (Liu et al, 2011). It is estimated that three quarters of all the aluminum produced since the 1880s is still in productive use (Bertram et al, 2009a).…”
Section: Methodsmentioning
confidence: 99%
“…Of course, this wonderful methodology was A considerable amount of information such as development situation, consumption, trade, recycling, and loss of aluminum industry can be obtained from SFA. Consequently, the information provide a base and support to design and make resource policies; many research fields are involved in the following: (1) analysis of quantities in the entire system-Chen researched the whole life cycle of aluminum including production, trade, consumption, stocks, and losses using the SFA method [8][9][10]15,29]; Buchner analyzed Austrian aluminum flows in 2010 using a static SFA model and conducted extensive research on aluminum production, consumption, trade, and waste management [30]; (2) recycling and sustainability-Melo developed several models (statistical approaches) for estimating the potential scrap arising from discard metal-containing products to predict the amount of aluminum old scrap in the waste management stage in Germany [31]; Boin and Bertram carried out mass balance analysis in the aluminum recycling industry for the EU-15 in 2002 [32]; Hatayama et al reported a dynamic SFA of aluminum and its alloying elements in Japan to estimate future quantities of discarded aluminum in each of the eight categories using a population balance model [33]; (3) combining with other aspects such as value chain and environment; Dhalström analyzed aluminum flows in the United Kingdom in 2001 combining SFA with economic and environmental dimensions to create a value chain analysis [34]; Gang developed a dynamic SFA model to simulate the stocks and flows of the U.S. aluminum cycle and analyze the corresponding greenhouse gas (GHG) emissions [13]. Of course, this wonderful methodology was also conducted to research other metals, such as copper [35][36][37][38][39][40], nickel [41], zinc [39,42,43], iron [26], lead [44,45], silver [46], phosphorus [47,48], and so on.…”
Section: Substance Flow Analysis (Sfa) and Brief Literature Reviewmentioning
confidence: 99%
“…The static fixed number of years for availability of bauxite in China is only 20 years or so according to the mining quantity in 2005 [12]. The bauxite in China has the properties of high aluminum, high silicon, and low aluminum-silicon ratio, which leads to difficulties in mining and smelting it; also, it consumes larger amounts of energy and discharges more pollution [13][14][15]. China imports substantial bauxite, and the external dependency has gone up gradually, from 19% in 1996 to 41.3% in 2014 (highest in 2011 at 53%).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that aluminum is the most abundant metallic element in the earth's crust and has widespread applications in modern life [15,16]. However, Al 3+ can cause harm to human beings when it is exposed to high concentration levels [17].…”
Section: Introductionmentioning
confidence: 99%